Optimizing Half Squat Postactivation Potential Load in Squat Jump Training for Eliciting Relative Maximal Power in Ski Jumpers - Gołaś, Artur; Wilk, Michal; Stastny, Petr; Maszczyk, Adam; Pajerska, Katarzyna; Zając, Adam (Journal of strength and conditioning research, 2017)
Gołaś, A, Wilk, M, Stastny, P, Maszczyk, A, Pajerska, K, and Zając, A. Optimizing half squat postactivation potential load in squat jump training for eliciting relative maximal power in ski jumpers. J Strength Cond Res 31(11): 3010-3017, 2017-Training load manipulation in a single workout session can increase or decrease training effectiveness in terms of athletes' strength or power gains. In ski jumping, the complex training that elicits maximal power gains may take advantage of the postactivation potentiation (PAP) mechanism. The aim of this research was to evaluate the changes in rate of force development (RFD), rate of power development (RPD), and jump height during a complex training session consisted of the barbell half squat (Sq) as a conditioning exercise with loads ranged between 60 and 100% of 1 repetition maximum (1RM), followed by a body weight squat jump (SqJ) as a performance task. The study was conducted with 16 elite athletes from the Polish National Ski Jumping Team, age 23 ± 8 years, body mass 56 ± 9 kg, and height 172 ± 12 cm. Complex training session started with the Sq at 60% of 1RM as the conditioning exercise, followed by 3 minutes of rest and the SqJ. The conditioning barbell half Sq was performed with 70, 80, 90, and 100% of 1RM with 5 minutes of rest. The differences in RFD occurred between an SqJ following the application of 80% of 1RM and all other SqJs (p = 0.01), and in RPD between SqJ without conditioning, SqJ after 60% of 1RM and 80% of 1RM (p = 0.02). On average, the most effective load in inducing PAP during ski jumpers' SqJ training is 80% of 1RM. The intensity of the conditioning exercise that elicits the greatest PAP effect should be individualized (60-100% 1RM), as it is dependent on the level of maximal strength.
Keywords: dospělí; zátěžový test; Adult; mladý dospělý; Rest; průřezové studie; Resistance Training; svalová síla; Adolescent; Sports Medicine; lidé; Skiing; odpočinek; Muscle Strength; lyžování; Cross-Sectional Studies; tělovýchovné lékařství; Male; Exercise Test; Young Adult; sportovci; Athletes; mužské pohlaví; mladiství; odporový trénink; Humans